High potassium exposure reveals the altered ability of astrocytes to regulate their volume in the aged hippocampus of GFAP/EGFP mice - Kolenicova, Denisa; Tureckova, Jana; Pukajova, Barbora; Harantova, Lenka; Kriska, Jan; Kirdajova, Denisa; Vorisek, Ivan; Kamenicka, Monika; Valihrach, Lukas; Androvic, Peter; Kubista, Mikael; Vargova, Lydia; et al. (Neurobiology of aging, 2020)
In this study, we focused on age-related changes in astrocyte functioning, predominantly on the ability of astrocytes to regulate their volume in response to a pathological stimulus, namely extracellular 50 mM K+ concentration. The aim of our project was to identify changes in the expression and function of transport proteins in the astrocytic membrane and properties of the extracellular space, triggered by aging. We used three-dimensional confocal morphometry, gene expression profiling, immunohistochemical analysis, and diffusion measurement in the hippocampal slices from 3-, 9-, 12-, and 18-month-old mice, in which astrocytes are visualized by enhanced green fluorescent protein under the control of the promoter for human glial fibrillary acidic protein. Combining a pharmacological approach and the quantification of astrocyte volume changes evoked by hyperkalemia, we found that marked diversity in the extent of astrocyte swelling in the hippocampus during aging is due to the gradually declining participation of Na+-K+-Cl- transporters, glutamate transporters (glutamate aspartate transporter and glutamate transporter 1), and volume-regulated anion channels. Interestingly, there was a redistribution of Na+-K+-Cl- cotransporter and glutamate transporters from astrocytic soma to processes. In addition, immunohistochemical analysis confirmed an age-dependent decrease in the content of Na+-K+-Cl- cotransporter in astrocytes. The overall extracellular volume changes revealed a similar age-dependent diversity during hyperkalemia as observed in astrocytes. In addition, the recovery of the extracellular space was markedly impaired in aged animals.
Keywords: Potassium; Aging; draslík; Cell Size; Astrocytes; velikost buňky; hipokampus; Potassium/glutamate uptake; Hippocampus; zelené fluorescenční proteiny; Animals; myši transgenní; Astrocyte; gliový fibrilární kyselý protein; zvířata; stárnutí; Glial Fibrillary Acidic Protein; Green Fluorescent Proteins; Volume regulation; astrocyty; Mice, Transgenic